AR Based Human Internal Organs for Education (International Journal of Scientific Research in Science and Technology, 2025)
The application of Augmented Reality (AR) in education is revolutionizing the way students engage with complex subjects, particularly in the fields of science and medicine. This paper explores the development and implementation of an AR-based educational tool focused on the visualization and understanding of human internal organs. The traditional methods of learning anatomy—such as textbooks, 2D diagrams, or even cadaver dissections—are often static, expensive, and limited in their capacity to offer interactive learning experiences. AR, however, provides an innovative solution that bridges these gaps by combining real-world environments with virtual 3D models, delivering an immersive learning experience that enhances comprehension and retention.
Keywords: Augmented Reality(AR); Organs; Internal; Models; Human